1995
DOI: 10.1128/iai.63.10.4078-4083.1995
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans cell walls contain the fluorescent cross-linking amino acid dityrosine

Abstract: Several clinical and laboratory isolates of Candida albicans have a natural blue surface fluorescence when cultured and observed with sensitive optics. The localization and color of the fluorescence are similar to those of the natural fluorescence of sporulated Saccharomyces cerevisiae which is caused by the generation and surface deposition of the cross-linking amino acid dityrosine. In S. cerevisiae, dityrosine production results from the direct action of at least two genes and is responsible for resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 40 publications
3
18
0
Order By: Relevance
“…Whereas there was hardly any fluorescence at pH 7, an intense fluorescence band at ;410 nm was observed at pH 11. The wavelengths of the excitation and emission peaks of the high pH solution matched those of the cross-linked amino acid dityrosine, presumably formed by cross-linking of the tyrosyl groups at the C-termini of pairs of 11-ala peptide chains (26). The pH dependence of the fluorescence spectra of the other two peptides (7-ala and 17-ala) were similar to those shown in Figs.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Whereas there was hardly any fluorescence at pH 7, an intense fluorescence band at ;410 nm was observed at pH 11. The wavelengths of the excitation and emission peaks of the high pH solution matched those of the cross-linked amino acid dityrosine, presumably formed by cross-linking of the tyrosyl groups at the C-termini of pairs of 11-ala peptide chains (26). The pH dependence of the fluorescence spectra of the other two peptides (7-ala and 17-ala) were similar to those shown in Figs.…”
Section: Resultssupporting
confidence: 71%
“…By measuring the optical density (OD) of the peptide solutions at pH 11 and using the extinction coefficients (e) of tyrosine and dityrosine at 284 nm (10,26), the final concentrations where (C Tyr ) ini is the initial concentration of tyrosine and was obtained by measuring the OD at pH 7, where very little of the tyrosine is expected to be dimerized. It was thus found that for both the peptides 11-ala and 17-ala, ;45% of the initial popu-lation of tyrosines at pH 7 formed dityrosine at pH 11, whereas the rest (55%) existed in the monomeric state.…”
Section: Resultsmentioning
confidence: 99%
“…It may be speculated that the lack of nutrients or pHshifts in the centre of a colony growing on an agar plate result in the synthesis of fluorophores like Dityrosin as described before, or in changed cell wall structures. [31][32][33] We were not able to determine a definitive reason for the autofluorescence, but were happy to find that there was hardly any autofluorescence, when yeasts were grown in broth. Under these conditions, all implemented probes were 100% sensitive ( Table 1).…”
Section: Fish By the Slide Chamber Methodsmentioning
confidence: 98%
“…Moreover, the sporulation-induced mug72 gene of S. pombe encodes an enzyme related to OSW2 [ 35 ], raising the possibility that the OSW2 -generated component of the S. cerevisiae spore wall is present in the S. pombe wall as well. The outer surface of the S. pombe wall is constructed from a protein rather than dityrosine [ 36 ]; however, many other ascomycete genomes carry orthologs to the dityrosine synthesis genes DIT1 and DIT2 as well as the dityrosine exporter DTR1 and dityrosine has been detected in several other yeasts [ 37 , 38 ]. Thus, the mechanisms of assembly and properties of the spore wall in S. cerevisiae are likely to be a useful model for ascospore walls in other ascomycetes.…”
Section: Discussionmentioning
confidence: 99%